The Influence of Using Accounting Information Systems and ECommerce on Entrepreneurial Decision Making : (Case Study of Accounting Students throughout Jember Regency) - Dewi, Nindi Kumala; Aspirandi, Rendy Mirwan; Afroh, Ibna Kamelia Fiel (Westscience Press, 2024)
This research was conducted with the aim of testing the influence of Accounting Information Systems and E-Commerce on entrepreneurial decision making among accounting students throughout Jember Regency. The population in this research is active Bachelor of Accounting students who have taken courses in accounting information systems and entrepreneurship, specifically for the class of 2020, at Muhammadiyah University Jember, Jember University, Kiai Haji Achmad Siddiq State Islamic University Jember, and Mandala Institute of Technology and Science Jember. The total population is 424 students. The sample selection technique uses Slovin's formula, with a sample size of 80 students in four universities. Data collection used primary data through distributing questionnaires online which obtained data from each university with the number of Muhammadiyah University Jember 13 students, University of Jember 25 students, UIN KHAS Jember 30 students, and ITS Mandala Jember 12 students. This research method uses quantitative methods with data testing carried out using SPSS version 27. The results of this research show that the accounting information system has a positive and significant effect on entrepreneurial decision making among accounting students in Jember Regency and e-commerce has a positive and significant effect on entrepreneurial decision making among accounting students in Jember Regency.